POKOK NGUDUD KERETEK: KEBIASAAN NGUDUD DAN MUNCULNYA ‘PABRIK KERETEK’ DI KEDIRI, JAWA TIMUR, 1970-AN - Ronal Ridhoi; Mohammad Nazri Adlani (Handep: Jurnal Sejarah dan Budaya, 2020)
Smoking, cigarette, and keretek have already been addiction to Indonesian peoples,especially in Kediri. Since the 1950s, Kediri has been recognized by its largest cigarettefactory, namely PT Gudang Garam. This study focuses on the linkages between ngudud(smoking) and ‘pabrik keretek’ (micro-scale cigarette factory), and why ngudud is stillexisted as a habit until nowadays. This research used historical method by perusing archives,online reports, articles, books, and interviews. This study indicates that ngudud was affectedby Chinese immigrants who introduced keretek to Kediri since the second half of 20th century,and it has a linkage to the emergence of ‘pabrik keretek’ on the next period. Ngudud, as ahabit, is still existed because keretek became more popular in 1970s and it has been usedfor daily activities and religious rituals in Kediri.